Interpretation of the Word of God contained in the Psalter. “Heretical”, Catholic or supra-denominational face of the translations of the psalms of Rej and Kochanowski - Wichowa, Maria (The Bible as a meeting place for Christian denominations, 2022)
“The Psalter” has a special status among the books of the “Bible”. There have been numerous translations of this work into national languages. During the Renaissance, translations into Polish appeared. The subject of research in this article are the prosaic Rej’s “Psalter” and the poetic by Kochanowski – a masterpiece of Renaissance religious poetry. The literary workshop of both translators was shown. They took into account the experiences of earlier translators, especially Erasmus of Rotterdam. Both Rej and Kochanowski tried not to ostentatiously manifest their religious beliefs. Their translations are of little help to Christians of different denominations. They took care of the over-denominational significance of their translations.